PENGEMBANGAN MADRASAH LITERAT BERBASIS PESANTREN - Mahmud, Ali (STAI Ma'had Aly Al-Hikam Malang, 2023)
Leaders have a very strategic role in the success of every program, including madrasa education institutions. The Head of Islamic Senior High School Muallimin Muallimat carries out his managerial role in initiating the development of literate school that is supported by all elements of the school. This study aims to determine the role of school principals in developing literate Islamic school based on the GELEM program guidelines formulated by the Ministry of Religion of East Java Province. The research method used was field research with a descriptive qualitative approach. The data collection technique was done by observation, interviews, and documentation. The data obtained were then aAbstract: This study aims to find out how the implementation of the madrasa literacy movement in Islamic boarding schools is based, then to also find out the factors that influence the development of madrasa literacy culture in Islamic boarding schools. The research method used is field research with a descriptive qualitative approach. The results of this study indicate that the implementation of the literacy movement at Madrasah Aliyah Muallimin Muallimat Tambakberas includes the habituation stage, the development stage and the learning stage. Then there are several factors that influence the development of a pesantren-based madrasah literacy culture, including psychosocial factors, leadership factors, environmental factors, organizational factors, ecological factors, and government policies. These factors tend to have a positive impact on the process of developing a literacy culture at Madrasah Aliyah Muallimin Muallimat Tambakberas. The novelty of this study is that the effective leadership factor of the madrasa head is the main factor for optimizing the development of a literacy culture by achieving 8 out of 9 indicators according to the Madrasah Literacy Movement program guidelinesnalyzed through the stages of data reduction, data presentation, and drawing conclusions. The results of this research indicate that there are several factors that influence the development of literacy culture islamic school, including psychosocial factors, leadership factors, environmental factors, organizational factors, ecological factors, and government policies. These factors tend to have a positive impact on the process of developing a literacy culture at Islamic Senior High School Muallimin Muallimat Tambakberas. The leadership role of the Islamic senior high school principal is the main foundation for optimizing the development of a literacy culture. The results of the study also showed that the leadership carried out by the Islamic school principal was quite good and effective, as evidenced by the achievement of 8 out of 9 indicators in accordance with the GELEM program guidelines.